Does acute pancreatitis herald pancreatic ductal adenocarcinoma? A multicenter electronic health research network study. (31st July 2022) - Singh, Ritu R.; Klein, Alison P.; Sharma, Neil R.; O'Reilly, Eileen M.
Abstract: Background and Objectives: High mortality in pancreas ductal adenocarcinoma (PDAC) is related to delayed diagnosis and lack of cost‐effective early detection strategies. Retrospective studies have demonstrated an association between PDAC and acute pancreatitis (AP). Herein, we explore the incidence of PDAC in patients with non‐biliary and non‐alcoholic AP. Methods: A population‐based, retrospective cohort study was conducted utilizing TriNetX (Cambridge, MA). Patients ≥40 years with AP (ICD‐10‐CM code: K85) and without biliary AP (K85.1), alcohol‐induced AP (K85.2) or chronic pancreatitis (K86.0, K86.1), were identified. The primary outcome was incidence of PDAC (C25) in patients at defined intervals following AP. We compared the rate of early‐stage diagnosis (stage 1–2) and surgical resection among patients with and without preceding AP. Results: The incidence of PDAC ranged from 2.16% (1 year) to 3.43% (5 years). Patients with PDAC and AP in preceding year were more likely to undergo surgical resection relative to those without AP (10.1% vs. 6.3%, risk ratio 1.62: 95% confidence interval, CI 1.47–1.79). Early‐stage diagnosis of PDAC was more frequent in patients with preceding AP; however, difference was insignificant ( p  = 0.48; 95% CI 0.64–2.58). Conclusion: AP is infrequently associated with PDAC and can precede a diagnosis of PDAC in a minority of patients without another known etiology of pancreatitis. Patients with a recent AP are more likely to undergo surgical resection of PDAC and a trend toward diagnosis at an earlier stage compared to patients with PDAC and without AP. The impact of AP‐related PDAC on survival is unknown. Abstract : Understanding the risk of pancreatic cancer following an acute pancreatitis diagnosis is a critical component to early intervention for pancreatic cancer in this high‐risk population as multiple data sets have demonstrated that early detection can lead to an increased percentage of patients diagnosed with stage I disease, and hence an improved chance for cure.